2020
DOI: 10.1111/1471-0528.16559
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, puerperium and perinatal constipation – an observational hybrid survey on pregnant and postpartum women and their age‐matched non‐pregnant controls

Abstract: Objective To evaluate the prevalence of constipation during pregnancy and early puerperium. Design Observational survey. Setting Secondary and tertiary hospital in Finland. Population Pregnant (n = 474) and postpartum (n = 403) women and a control group of 200 non‐pregnant women who did not give birth in the past year. Methods Women reported bowel function and other gastrointestinal symptoms on a structured questionnaire using an 11‐point numerical rating scale (0 = no symptom, 10 = most severe symptom) and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…When prevalence was assessed based on survey respondent self-reporting, 61% reported constipation in the second trimester, 55% in the third trimester, and 77% and 88% a few days after vaginal or caesarean deliveries, respectively. By 1 month postpartum, constipation was self-reported in approximately 30% for both delivery types, which was similar to the self-reported incidence of 37% in the control group (9).…”
Section: Constipation In Pregnancysupporting
confidence: 75%
See 1 more Smart Citation
“…When prevalence was assessed based on survey respondent self-reporting, 61% reported constipation in the second trimester, 55% in the third trimester, and 77% and 88% a few days after vaginal or caesarean deliveries, respectively. By 1 month postpartum, constipation was self-reported in approximately 30% for both delivery types, which was similar to the self-reported incidence of 37% in the control group (9).…”
Section: Constipation In Pregnancysupporting
confidence: 75%
“…Despite this high frequency, constipation during and after pregnancy is often neglected (8). A recent survey study involving 1,078 participants from Finland used modified Rome IV criteria (symptoms with 25% of defecations over 3 months) and reported a prevalence of constipation in 40% of pregnant and 52% of postpartum women, compared with only 21% in nonpregnant and similarly aged controls (9). Rates were not significantly different between the second and third trimesters.…”
Section: Constipation In Pregnancymentioning
confidence: 99%
“…The constipation diagnosis was found in three studies included in this review. Constipation is related to bad eating habits, such as low fiber and water intake, and a low or nonexistent relationship with physical activity (34). In turn, a research study (35) showed that a sedentary lifestyle and a Body Mass Index greater than 24 influence intestinal transit, leading to constipation in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Other conditions that are common are anal fissure in the second trimester (10.6%), haemorrhoidal prolapse in the third trimester (14.4%), haemorrhoidal thrombosis immediately post partum (14.6%) and postpartum anal fissure at 3 months (9.6%) 13. A recent survey study involving 1078 Finnish women using modified Rome IV criteria (symptoms with 25% of defecations over 3 months) reported a prevalence of constipation in 40% of pregnant and 52% of postpartum women, compared with only 21% in non-pregnant and similarly aged controls 14. Rates were not significantly different between the second and third trimesters.…”
Section: Introductionmentioning
confidence: 99%